PENDIDIKAN INKLUSIF DAN AKSEBILITAS DALAM PENDIDIKAN ISLAM - Desriadi; Solihah Titin Sumanti (Program Studi Manajemen Pendidikan Islam, 2022)
Learning for children with special needs requires special skills. A teacher, in addition to delivering Islamic Education Accessibility Learning, must also be able to observe the unique talents and interests of children with special needs. This study aims to analyze the implementation of Islamic education accessibility learning for children with special needs. This study was conducted at the Safinatussalamah Border Dayah located in Aceh Singkil Regency using a boarding school education system. This study uses a qualitative case study approach. Data collection through observation, interview and document study techniques. To analyze the data using qualitative analysis techniques with the steps of data exposure, data reduction, and drawing conclusions. The results of the analysis found that accessibility in Islamic Religious Education teaching is the key to providing equal opportunities for all individuals, including people with disabilities, to live and understand their Islamic religion. The implementation of Islamic Religious Education learning at the Safinatussalamah Border Dayah located in Aceh Singkil Regency. children with special needs requires an inclusive approach, to create an inclusive approach it is necessary to understand the needs and characteristics of diverse children. This can be done by doing; curriculum adjustment, collaboration with special education specialists, use of educational technology, inclusive learning approaches and field observations as reference data in implementing Islamic Religious Education learning for children with special needs